Inherited L1 Retrotransposon Insertions Associated With Risk for Schizophrenia and Bipolar Disorder. Issue 1 (14th July 2021) - Reiner, Benjamin C; Doyle, Glenn A; Weller, Andrew E; Levinson, Rachel N; Rao, Aditya M; Davila Perea, Emilie; Namoglu, Esin; Pigeon, Alicia; Arauco-Shapiro, Gabriella; Weickert, Cyndi Shannon; Turecki, Gustavo; Crist, Richard C; et al.
Abstract: Studies of the genetic heritability of schizophrenia and bipolar disorder examining single nucleotide polymorphisms (SNPs) and copy number variations have failed to explain a large portion of the genetic liability, resulting in substantial missing heritability. Long interspersed element 1 (L1) retrotransposons are a type of inherited polymorphic variant that may be associated with risk for schizophrenia and bipolar disorder. We performed REBELseq, a genome wide assay for L1 sequences, on DNA from male and female persons with schizophrenia and controls ( n = 63 each) to identify inherited L1 insertions and validated priority insertions. L1 insertions of interest were genotyped in DNA from a replication cohort of persons with schizophrenia, bipolar disorder, and controls ( n = 2268 each) to examine differences in carrier frequencies. We identified an inherited L1 insertion in ARHGAP24 and a quadallelic SNP (rs74169643) inside an L1 insertion in SNTG2 that are associated with risk for developing schizophrenia and bipolar disorder (all odds ratios ~1.2). Pathway analysis identified 15 gene ontologies that were differentially affected by L1 burden, including multiple ontologies related to glutamatergic signaling and immune function, which have been previously associated with schizophrenia. These findings provide further evidence supporting the role of inherited repetitive genetic elements in the heritability of psychiatric disorders.